Guest Editors' Introduction and Overview: IRT-Based Cognitive Diagnostic Models and Related Methods - DiBello, Louis V.; Stout, William (Journal of educational measurement, 2007)
Much of the 20th century psychometric focus on testing has been on the unidimensional continuous scaling of examinees in major subject or cognitive areas, such as verbal reasoning, mathematics ability, etc., often using item response theory (IRT) modeling, especially IPL, 2PL, 3PL modeling. In fact, many of the well-known, currently nationally administered, standardized tests in America are supported wholly or in part by such continuous unidimensional IRT models.